(untitled) (ARQUISUR Revista, 2020)
The state promotion of Argentine architectural and infrastructure works in the "long 1960s" was linked to recognizable demands that emerge from territorial and economic planning. The deepening of the industrialization process implied an energy self-sufficiency country, fluent communication between production centers and the newly created provincial states, as well as the construction industrialization. These aspects had an impact on the creation and development of various construction programs. However, this article reviews the literature around three specific programs: industry, energy and territorial connections, for considering them fundamental and synergistic within the industrialization process in its second phase. In the disciplinary gaze on the object of study, politics and economics agree quite a bit on the conceptualization of the period, planning incorporates the notion of imbalance characterizing the Argentine territory, and from architecture the works have been approached only in terms of search for national identity and modern style questions. This work allows us to point out that the theoretical construction revolves around the notions of: developmentalism as a theoretical model, territory as geographical space and place of power, planning as a priority discipline at the time and architecture for progress as a concept under construction.